Multipotential Surface Elastoplastic Constitutive Model and Its Application in the Analysis of the Phase II Cofferdam of the Three Gorges Project - Yong Wen; Guanghua Yang; Zhihui Zhong (Geofluids)
Based on multipotential surface theory, an elastoplastic constitutive model is established in this paper. The required parameters of the proposed model are the same as those of the Duncan-Chang model, and the proposed model is no longer restricted by the generalized form of Hooke’s law. In addition, the proposed model uses a numerical method to fit the test curves to determine the required parameters. The calculation program of the proposed model is also developed by FLAC3D, and according to the comparison with the triaxial test results of gravel and the stress and deformation analysis of the phase II cofferdam of the Three Gorges Project, the rationality and superiority of the proposed model are verified.